Building porphyrin-based MOFs on MXenes for ppb-level NO sensing. Issue 13 (9th March 2023) - Chang, Yanwei; Chen, Minyi; Fu, Zijing; Lu, Ruofei; Gao, Yixun; Chen, Fengjia; Li, Hao; Frans de Rooij, Nicolaas; Lee, Yi-Kuen; Wang, Yao; Zhou, Guofu
Abstract : Based on the idea of facilitating charge transfer by constructing a Schottky junction, we assembled a porphyrin-based MOF (Co-TCPP(Fe)) with Mxene (Ti3 C2 T x ) through hydrogen bonding to offer a high-performance chemiresistive NO sensing hybrid. Abstract : Fractional exhaled nitric oxide (FeNO) is a significant biological signaling molecule. However, the detection of ppb-level nitric oxide (NO) still faces great challenges. Herein, we designed and prepared a porphyrin-based MOF (Co-TCPP(Fe)) with rod-like morphology which was assembled with MXene (Ti3 C2 T x ) through hydrogen bonding to offer a kind of chemiresistive NO sensing hybrid (Co-TCPP(Fe)/Ti3 C2 T x ). The Co-TCPP(Fe)/Ti3 C2 T x -20 based sensor showed superior NO sensing performance at room temperature including high response ( R a / R g = 2.0, 10 ppm), reliable repeatability, high selectivity, low practical limit of detection (pLOD, 200 ppb), and fast room temperature NO sensing response/recovery speed (95 s/15 s, 10 ppm). The study of the gas sensing mechanism demonstrated that reviving more unoccupied Fe–N4 units to sense NO by forming a rod-like MOF architecture and facilitating charge transfer by constructing a Schottky junction of Co-TCPP(Fe)/Ti3 C2 T x jointly contribute to the superior performance of the obtained Co-TCPP(Fe)/Ti3 C2 T x based NO sensor. This work not only paves an avenue for fabricating bimetallic porphyrin-based rod-like MOFs, but also proposes a facile strategy of constructing Schottky junctions between MOFs and MXenes for high-performance chemiresistive gas sensors, which acts as a guide for fabricating MOF-based hybrid sensing materials in the future.